Updates on treatment options in aspirin exacerbated respiratory disease. Issue 1 (February 2022) - Ramos, Courtney L.; Woessner, Katharine M.
Abstract : Purpose of review: The aim is to describe why this review is timely and relevant. Acetylsalicylic acid exacerbated respiratory disease (AERD) is a clinically significant disease affecting approximately 7% of all asthmatics or around 1, 400, 000 persons in the United States alone. A large portion of these patients remain undiagnosed. This review summarizes up to date knowledge on the pathophysiology, treatment opinions and provides an expert opinion on how to approach the AERD patient. Recent findings: Findings describe the main themes in the literature covered by the article. Review of the current knowledge in terms of the key cells, cytokines/chemokines contributing to the acquired disease state of AERD. It also provides clinical approach toward the AERD patient with regards to current treatment options. Summary: Summary describes the implications of the findings for clinical practice or research. This is an up-to-date review of the current literature, with insight into how to approach the management of an AERD patient.